Threshold and recovery of anaerobic digestion under high ammonia stress: influence of COD/NH4+ ratio and CO2 enrichment - Javad Bardi, Mohammad; Müller, Felix; Polag, Daniela; Habtu, Nigus G.; Koch, Konrad (Bioresource technology, 2025)
This study underscores the importance of maintaining an optimal chemical oxygen demand to ammonia (COD/NH4+) ratio to ensure stable anaerobic digestion (AD) performance. The optimal COD/NH4+ ratio ranges from 24.0 to 33.0, while a critical threshold is identified between 11.0 and 17.0, below which AD performance declines. However, the AD of protein-rich substrates typically operates under an “inhibited steady-state” condition, characterized by a lower COD/NH4+ level. At lower COD/NH4+ ratios, the acetoclastic methanogenesis is inhibited, while hydrogenotrophic methanogens remain active, as evidenced by an increase of over 96 mUr in δ2H-CH4 isotope values. The CO2 enrichment of AD under lower COD/NH4+ ratios demonstrate to be a promising approach for AD recovery and performance stabilization. The CO2 enrichment showed a rapid full recovery in methane production at a COD/NH4+ ratio as low as 7.0 (6.2 gNH4+-N/L) and a slower but still effective recovery up to a COD/NH4+ ratio of 5.0 (10 gNH4+-N/L). The δ2H-CH4 isotope values from CO2-enriched ADs indicated a well-balanced methanogenic community, in contrast to non-enriched ADs, which exhibited clearly lower acetoclastic activity. Therefore, CO2 enrichment is promising for enhancing AD recovery and stability at high ammonia stress, promoting methanogenic balance and boosting methane production.
Im Titel ist bei COD/NH4+ die 4 tiefgestellt und das Pluszeichen hochgestellt, bei CO2 ist die 2 tiefgestellt
Online verfügbar: 16. Juni 2025, Artikelversion: 19. Juni 2025
Gesehen am 18.11.2025